2001
DOI: 10.1177/088307380101600615
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Findings in Patients With Severe Neonatal Indirect Hyperbilirubinemia

Abstract: The aim of this study was to document the magnetic resonance imaging (MRI) findings of cases with a history of severe neonatal indirect hyperbilirubinemia. Ten cases (eight cases with neurologic findings, two normal cases) with a history of severe neonatal indirect hyperbilirubinemia were studied. Neurologic findings and MRI results were described and correlated. Seven of eight cases with neurologic findings demonstrated symmetric and uniform increased T2 signal changes limited to globus pallidi. MRI scans of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Maximum serum indirect bilirubin level of our patient was 35 mg/dl and the aetiology of jaundice was Rh isoimmunisation. Serum bilirubin levels of reported patients were between 17.7 and 50 mg/dl, and the aetiologies of jaundice were Rh and ABO incompatibility, G6PD deficiency and unknown causes [2,3,4,5,6,7,12]. There may be other factors, except for serum indirect bilirubin level and the aetiology of hyperbilirubinemia, that affect the neuroradiological findings of patients with kernicterus.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Maximum serum indirect bilirubin level of our patient was 35 mg/dl and the aetiology of jaundice was Rh isoimmunisation. Serum bilirubin levels of reported patients were between 17.7 and 50 mg/dl, and the aetiologies of jaundice were Rh and ABO incompatibility, G6PD deficiency and unknown causes [2,3,4,5,6,7,12]. There may be other factors, except for serum indirect bilirubin level and the aetiology of hyperbilirubinemia, that affect the neuroradiological findings of patients with kernicterus.…”
Section: Discussionmentioning
confidence: 95%
“…Bilateral symmetrical high signals in the globus pallidus on T2-weighted images are the most common reported findings [2,3,4,5,6,7]. Steinborn et al reported symmetrical signal intensity changes in the subthalamic nucleus in addition to the globus pallidus on T2-weighted images in a patient with kernicterus [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although kernicterus affects various parts of the central nervous system, only the GP demonstrates remarkable signal changes with MR imaging [7]. The most commonly reported and characteristic MR imaging finding of kernicterus, after the acute period, is bilateral hyperintense GP lesions on T2-weighted MR images.…”
Section: Discussionmentioning
confidence: 99%
“…70 Bilirubin is a toxin that targets the globus pallidus, 71 rather than the putamen-thalamus, as in HIE. This is another example of the concept of selective vulnerability, and supports the importance of imaging to determine lesion location.…”
Section: Neonatal Encephalopathymentioning
confidence: 99%